2015
DOI: 10.1001/jamaneurol.2015.1584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Presymptomatic Body Mass Index and Consumption of Fat and Alcohol on Amyotrophic Lateral Sclerosis

Abstract: IMPORTANCE Because dietary intake may influence pathophysiologic mechanisms in sporadic amyotrophic lateral sclerosis (ALS), the association between premorbid dietary intake and the risk of sporadic ALS will provide insight into which mechanisms are possibly involved in ALS pathophogenesis.OBJECTIVE To systematically determine the association between premorbid dietary intake and the risk of sporadic ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 46 publications
3
74
3
Order By: Relevance
“…Data on fat metabolism in these populations with undiagnosed ALS are limited. Notably, higher premorbid consumption of fat contributes to an increased risk of ALS; a potential mechanism is that high fat intake leads to dyslipidemia, subsequently increasing the risk of ALS. Previous MR studies have demonstrated that higher low‐density lipoprotein increases the risk of ALS .…”
Section: Discussionmentioning
confidence: 99%
“…Data on fat metabolism in these populations with undiagnosed ALS are limited. Notably, higher premorbid consumption of fat contributes to an increased risk of ALS; a potential mechanism is that high fat intake leads to dyslipidemia, subsequently increasing the risk of ALS. Previous MR studies have demonstrated that higher low‐density lipoprotein increases the risk of ALS .…”
Section: Discussionmentioning
confidence: 99%
“…The first study28 recruited 494 patients with incident ALS and 1599 controls from 2006to2009, and found that current alcohol consumption was associated with halved ALS risk (OR 0.52), while no significant association was found among former alcohol drinkers (OR 0.67). The second study29 enrolled a larger sample of patients and controls from 2006to2011, and found that alcohol drinkers were significantly less likely to develop ALS (OR 0.91, p=0.03). In addition, a Swedish cohort study, which examined the association between ALS onset and alcohol intake using hospital discharge records of all Swedish residents,30 found that subjects affected by alcohol use disorders (AUD) showed a decreased risk of ALS compared with those without AUD, with a significant standardised incidence ratio of 0.54(95%CI0.45 to0.63).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have elegantly demonstrated the profound metabolic alterations long before the onset of motor symptoms . Disturbed energy metabolism, in terms of altered body mass index (BMI), energy intake, and fat consumption, has recently also been demonstrated in ALS patients before the onset of motor symptoms . In the present cohort study of more than 20 years of follow‐up, we assessed the associations of several carbohydrate and lipid biomarkers with the future risk of ALS.…”
Section: A Summary Of Previous Studies On Blood Biomarkers Of Carbohymentioning
confidence: 99%
“…8,14 Disturbed energy metabolism, in terms of altered body mass index (BMI), energy intake, and fat consumption, has recently also been demonstrated in ALS patients before the onset of motor symptoms. 15 In the present cohort study of more than 20 years of follow-up, we assessed the associations of several carbohydrate and lipid biomarkers with the future risk of ALS. More important, we examined, for the first time, the associations of apolipoprotein B (apoB; atherogenic) and apolipoprotein A-I (apoA-I; atheroprotective) with ALS risk.…”
mentioning
confidence: 99%